First report of a blue hue Schendylops (Geophilomorpha, Schendylidae), with a description of a new species from Southeastern Brazil - Calvanese, Victor C.; Brescovit, Antonio D. (Zootaxa, 2019)
The first report of a blue colored body in schendylid specimens is presented based on a description of Schendylops turmalina sp. nov. recorded from Southeastern Brazil. The female holotype is described and illustrated, and the variations observed in male paratypes and in a juvenile male from the same locality are given. The new species is characterized by having adults with an uninterrupted series of sternal pore-fields, from the first to the penultimate leg-bearing segments, undivided on the anterior and posterior part of the body and divided into two sub-symmetrical areas in the middle region. This characteristic can also be observed in Schendylops tropicus, S. coscaroni, S. parahyhae, S. inquilinus, S. grismadoi and S. demelloi. However, in addition to the blue hue present between the first and ultimate leg-bearing segments, S. turmalina sp. nov. differs from all the aforementioned species in having the following unique characteristics: antennae less than 2.5 times the length of the cephalic plate in both male and female; posterior margin of mid-part of labrum near-straight; forcipular tarsungulum with the internal edge serrate; tarsus 2 of the ultimate pair of legs with an apical tubercle which has two pore-like sensilla and is surrounded by two larger sensilla.